A profile of the hospitality industry - Stringam, Betsy Bender; Partlow, Charles G. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
The hospitality industry is generally referred to as businesses that provide accommodation and foodservice. Traditionally an entrepreneurial business, it now includes organizations ranging from small independent cafes to large multinational corporations. Businesses in the hospitality industry have many organizational structures to include whole ownership, franchising, consortia, and management contracts as key configurations. Affected by capital investment, travel and tourism trends, threats and opportunities, the hospitality industry has proved resilient.
1. Introduction -- 2. How the industry operates -- 3. Industry organization and competition -- 4. Uniqueness of the hospitality product -- 5. Competitive strategies -- 6. Outside market forces -- 7. Challenges and opportunities for the industry -- Resources for further study -- References -- Endnotes -- Index.
Includes bibliographical references (pages 131-164) and index.
Title from PDF title page (viewed on November 30, 2015).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Hospitality industry; Hospitality; Hotel; Motel; Inn; Resort; Restaurant; Foodservice; Quick Service; Lodging; Catering; Gaming; Casino; Tourism; Electronic books